Pengenalan Objek Bersejarah Pada Museum Sang Nila Utama Kota Pekanbaru Menggunakan Teknologi Augmented Reality Berbasis Android - Kurniawan Kurniawan; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Sang Nila Utama Museum is a regional museum located in Riau Province that stores and exhibits historical objects, especially objects used by indigenous tribes in Riau. To make it easier for visitors to find out information about historic objects, software application is made with Augmented Reality (AR) Technology. This application implements the method of Marker Based Tracking and Markerless Augmented Reality. Several stages of application designed such as collecting data from the Technical Implementation Unit (UPT) of the Sang Nila Utama Museum like as design an interface, buliding up and database and information displayed, put in the application designed in to Android package (Apk). To build this designed application, tools such as Unity 3D, Vuforia Object Scanner, Vuforia SDK, Android SDK, Java Development Kit, Adobe Photoshop, and Adobe Premiere Pro are used. This research produces Augmented Reality application designed based on Android that can display information in the form of text and videos about historical objectsKeywords: Augmented Reality, Based Tracking Marker, Markerless Augmented Reality, Main Sang Nila Museum, Historic Objects